DARI EDUKASI KE AKSI: PENGUATAN JIWA WIRAUSAHA KOMPETITIF BAGI CALON DAN PELAKU UMKM DI YAYASAN GLOBAL CAHAYA NUBUWWAH INSANI (GCNI) BOARDING SCHOOL PURWAKARTA - Nurhayati; Retno Sari Murtiningsih; Kurniawati Kurniawati; Syifa Khairana; Dewi Anggraeni; Gavrila Indra Saputra; Ana Rosalinda (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This Community Service Program (PKM) aims to develop a competitive entrepreneurial mindset among prospective and existing MSME actors at GCNI Boarding School, Purwakarta. The program is motivated by several institutional challenges, including the low number of students, limited accommodation occupancy rates, a low number of coffee shop visitors, and suboptimal productivity and sales of cultivation-based businesses. The implementation method uses an educational and participatory approach through systematically designed entrepreneurship training and counseling activities. Program evaluation was conducted using a pre-test and post-test design involving 25 participants to measure improvements in understanding. The results of the paired sample t-test indicate a significant increase in knowledge after the training, with the mean score rising from 2.20 to 5.60 and a significance value of 0.000 (p < 0.05). These findings demonstrate that the PKM program is effective in improving participants’ understanding, skills, and readiness to become competitive MSME entrepreneurs.